Analysis of Gadget Addiction and Its Impact on Students’ Learning Motivation in the Aqidah Akhlaq Subject among Grade VI Students at MI Muhammadiyah Malua - Alwiah Alwiah; Elihami; Achmad Dahlan (Edumaspul: Jurnal Pendidikan, 2026)
This study aims to describe the influence of gadget addiction on students’ learning motivation in the Akidah Akhlak subject of sixth grade students at MI Muhammadiyah Malua. This research uses a descriptive qualitative method with the research subjects consisting of sixth grade students, Akidah Akhlak subject teachers, and students’ parents. Data collection techniques were carried out through interviews, observations, and documentation. The results of the study show that most students experience gadget addiction 55,6%, which is indicated by excessive use for playing games and social media, thus decreasing their learning motivation, especially in the Akidah Akhlak subject. However, the directed use of gadgets under the supervision of teachers and parents can have a positive impact as an engaging learning medium. Thus, gadget addiction has a negative influence on students’ learning motivation, but it can be minimized through supervision and the educational use of gadgets